The Influence of Muslim Endorsers and Influencers in Promoting Halal Tourist Attractions. - Setiawan, Harry; Purmono , Bintoro Bagus (JEMBA: Journal of Economics, Management, Business and Accounting, 2023)
This study aimed to analyze the influence of Muslim influencers, Muslim endorsements, and destination image on Muslim tourists’ visit intention. Based on data analysis from 206 respondents, it was discovered that Muslim endorsements had a positive and significant effect on visit intention, while the influence of Muslim influencers was positive but not significant. Meanwhile, destination image had a positive but not significant influence on visit intention, and did not mediate the effects of Muslim influencers and endorsements. Thus, Muslim endorsements become an important factor that can directly increase Muslim tourists’ visit intention. Marketing strategies that put forward Muslim endorsements are needed to attract Muslim tourists to visit.